Terapi Aktivitas Kelompok (TAK) Stimulasi Persepsi Meningkatkan Harga Diri Anak di Lembaga Pemasyarakatan - Ah. Yusuf; Rizki Fitryasari; Wiwin Sulistyawati (Jurnal Ners, 2007)
Introduction: Prison is societal implementer unit which accommodate care and develop the delinquent children. It was recorded that 57% of children at Blitar Child Prison undergo some self concept problems such as low self esteem. This was caused by some factors such as society’s stigmatization toward criminals, development pattern and education, and less support from family. If the self esteem problem is not being overcome soon, the children may  fell useless, disable to control their self and recrime when they are back to society. The objective of this study was to analyze the influence of  GAT (Group Activity Therapy) perception stimulation in increasing the children  self esteem at prison. Method:  A quasy experimental pre post control design was used in this study. Samples were recruited by using total sampling and there were 22 samples as on inclusion criteria. The independent variable was GAT perception stimulation and the dependent variable was increasing self esteem of these childen. Data were collected by using questionnare and analyzed by using Wilcoxon Signed Ranks Test and Mann Whitney U Test with the significance level α≤0.05.Result:  The result showed that controlled group has significance level was p=0.654, it is mean there was no self esteem change before and after GAT perception stimulation was given. Whereas treatment group has significance level was p=0.001, it revealed that  there was self esteem change before and after GAT perception stimulation was given. The result of Mann Whitney U Test showed p=0.000 which means was accepted. Discussion: It can be concluded that perception stimulation can increase the children self esteem at prison. Further studies are recommended to study the effect of GAT perception stimulation modified by skill therapy in increasing children self esteem in prison.